Management and Administration of School Libraries - Juairiah, Juairiah; Halimah, Hayatul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study discusses the management of the school library at SMP Negeri 2 Alalak, focusing on the service sector based on management theory and in alignment with national standards for junior high schools. The purpose of this study is to examine the management of the school library at SMP Negeri 2 Alalak, particularly in terms of library services based on management theory and conformity with national standards for junior high school libraries, as well as to identify the challenges encountered in managing library services at SMP Negeri 2 Alalak. The research findings indicate that the management of the school library at SMP Negeri 2 Alalak has not yet fully met the national library standards. Library services are still conducted manually and have not adapted to technological developments through the integration of information technology in service delivery. However, library programs in the form of literacy activities conducted in collaboration with Indonesian language teachers serve as efforts to improve students’ reading abilities. The implication of this study is that it provides insights for school library managers in improving library services to increase library visits.